A Robotic Device for Measuring Human Ankle Motion Sense - Qiyin Huang; Bin Zhong; Naveen Elangovan; Mingming Zhang; Jurgen Konczak (IEEE, 2023)
Proprioceptive signals about ankle motion are essential for the control of balance and gait. However, objective, accurate methods for testing ankle motion sense in clinical settings are not established. This study presents a fast and accurate method to assess human ankle motion sense acuity. A one degree-of-freedom (DOF) robotic device was used to passively rotate the ankle under controlled conditions and applied a psychophysical forced-choice paradigm. Twenty healthy participants were recruited for study participation. Within a trial, participants experienced one of three reference velocities (10°/s, 15°/s, and 20°/s), and a smaller comparison velocity. Subsequently, they verbally indicated which of the two movements was faster. As outcome measures, a just-noticeable-difference (JND) threshold and interval of uncertainty (IU) were derived from the psychometric stimulus-response difference function for each participant. Our data show that mean JND threshold increased almost linearly from 0.53°/s at the 10°/s reference to 1.6°/s at 20°/s ( ${p} < 0.0001$ ). Perceptual uncertainty increased similarly (median IU = 0.33°/s at 10°/s and 0.97°/s at 20°/s; ${p} < 0.0001$ ). Both measures were strongly correlated ( ${r} _{s}$ = 0.70). This implies that the bias of the human ankle motion sense is approximately 5 - 8% of the experienced movement velocity. We demonstrate that this robot-aided test produces quantitative data on human ankle motion sense acuity. It provides a useful addition to the current measures of ankle proprioceptive function.